2019
DOI: 10.1021/acs.jafc.9b01123
|View full text |Cite
|
Sign up to set email alerts
|

Improved Thermostability of Maltooligosyltrehalose Synthase from Arthrobacter ramosus by Directed Evolution and Site-Directed Mutagenesis

Abstract: Maltooligosyltrehalose synthase (MTSase) is a key enzyme in trehalose production. MTSase from Arthrobacter ramosus has poor thermostability, limiting its industrial use. In this study, mutant G415P was obtained by directed evolution and S361R/S444E was subsequently generated based on a structure analysis of the region around G415. The t 1/2 of G415P and S361R/S444E at 60 °C increased by 3.0-and 3.2-fold, respectively, compared with the wild-type enzyme. A triple mutant (G415P/S361R/S444E) was obtained through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The modeled structure of IEM showed that K83, K95, and L273 were all located on the protein surface (Figure 5a), which was consistent with the opinion that irreversible thermal denaturation of a protein usually contained an unfolding step and such process primarily involved surface-located regions [40]. Intramolecular interactions including hydrogen bonds, salt bridges, and disulfide bonds had pivotal roles in enhancing the thermal stability of proteins [25,26,28]. When the distance between two polar non-hydrogen atoms was less than 3.5 Å, a hydrogen bond which contributed 0.6 kcal/mol energy to protein stability could be formed [41].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The modeled structure of IEM showed that K83, K95, and L273 were all located on the protein surface (Figure 5a), which was consistent with the opinion that irreversible thermal denaturation of a protein usually contained an unfolding step and such process primarily involved surface-located regions [40]. Intramolecular interactions including hydrogen bonds, salt bridges, and disulfide bonds had pivotal roles in enhancing the thermal stability of proteins [25,26,28]. When the distance between two polar non-hydrogen atoms was less than 3.5 Å, a hydrogen bond which contributed 0.6 kcal/mol energy to protein stability could be formed [41].…”
Section: Discussionsupporting
confidence: 78%
“…Directed evolution is a useful protein engineering method [23], and numerous researches enhanced enzymes' performances at elevated temperatures by employing errorprone PCR [24,25]. However, it is very time-consuming to screen large mutant pools, especially for those enzymes without efficient high-throughput screening approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the directed mutagenesis breeding technology has been developed rapidly in the past decade, the random chemical and physical mutagenesis breeding technologies still play an important role in obtaining organisms with high enzymic activities or ideal properties. Recently, ARTP, a newly developed mutation system, has shown great potential in microbe breeding. Its core component is a helium radio-frequency atmospheric-pressure glow discharge (RF APGD) plasma generator .…”
Section: Introductionmentioning
confidence: 99%
“…Q36 MTSase is similar to those of the MTSases from A. ramosus (Ar-MTSase; PDB entry 6LCU), Sulfolobus acidocaldarius (Sa-MTSase; PDB entry liv8), Sulfolobus shibatae DSM5389 (5389-GTSase; PDB entry 5zcr) and Sulfolobus tokodaii (St-MTSase; PDB entry 3hje). [27][28][29][30][31] The MTSase first split the C1-O bond of the glucoside linkage at the reducing end of the substrate. [32] The glycosyl-enzyme intermediate was formed after glycosyl residue bound to the enzyme, and the glycosyl reside was transferred to the glucose in the cleft by the -1,1-linkage.…”
Section: Preparation Of 3-o--d-glucosyl Trehalose From 4--nigerosyl-glucosementioning
confidence: 99%